Implementation of Aqidah Akhlaq Learning in the Merdeka Curriculum: Implementasi Pembelajaran Aqidah Akhlaq dalam Kurikulum Merdeka - Indiyani, Indiyani; Rindaningsih, Ida (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Character education, particularly in the context of Aqidah Akhlaq, plays a vital role in shaping students’ moral and spiritual values in Islamic primary education. Specific Background: The implementation of the Merdeka Curriculum emphasizes flexibility in learning design to accommodate students’ needs, including integrating religious values in daily practice. Knowledge Gap: Previous studies have discussed character formation in Islamic education, but limited research has described in detail how Aqidah Akhlaq learning is practically implemented within the Merdeka Curriculum in specific school contexts. Aims: This study aims to describe the implementation of Aqidah Akhlaq learning and its outcomes at MI Ma’arif Pagerwojo, Sidoarjo. Results: Using a qualitative phenomenological approach with observation, interviews, documentation, and questionnaires, the study found that Aqidah Akhlaq learning is conducted both inside and outside the classroom, supported by structured lesson plans, varied learning methods, and a school-wide 6S culture. Students became more active, understood the lessons better, and showed improved behavior. Novelty: This research provides contextual insights into integrating Aqidah Akhlaq into the Merdeka Curriculum through both formal instruction and habitual practice. Implications: The findings offer practical references for teachers and schools in developing religious-based character education aligned with national curriculum reforms. Highlights : Contextual integration of Aqidah Akhlaq in the Merdeka Curriculum Combination of classroom learning and habitual practice Positive behavioral changes in students Keywords: Merdeka Curriculum, Aqidah Akhlaq, Character Education, Islamic Primary School, Phenomenology